Frequency of Methicillin-Resistant Staphylococcus aureus (MRSA) in Pediatric Skin and Soft Tissue Infections and Its Antibiotic Susceptibility - Syed Bilal Hussain Shah, Muhammad Maroof Ali, Sumaira Shouket, Asma Afzal, Aamir Sohail (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of skin and soft tissue infections (SSTIs) in pediatric populations. Objective: This study aims to assess the frequency of MRSA in pediatric SSTIs and its antibiotic susceptibility profile, contributing to a better understanding of local resistance patterns and guiding clinical treatment strategies. Methods: A cross-sectional observational study was conducted at The Children’s Hospital, Lahore from November 2022 to April 2023. A total of 165 pediatric patients aged 1 month to 18 years with clinically diagnosed SSTIs were enrolled. Microbiological samples were collected from infected sites for culture and identification of S. aureus. MRSA was confirmed using the disk diffusion method, and antibiotic susceptibility testing was performed using the Kirby-Bauer method. Results: Of the 150 S. aureus isolates, 120 (73%) were identified as MRSA. The highest prevalence of MRSA was found in abscesses (85%) and cellulitis (80%). Antibiotic susceptibility testing revealed that MRSA strains were highly susceptible to vancomycin (98%) and linezolid (92%). However, significant resistance was observed to erythromycin (56%), tetracycline (49%), and trimethoprim-sulfamethoxazole (30%). The prevalence of MRSA was higher in patients with recurrent skin infections (65%) compared to first episodes (48%). Conclusion: MRSA is a predominant cause of pediatric SSTIs, with high resistance to commonly used oral antibiotics such as erythromycin and tetracycline. Vancomycin and linezolid remain highly effective treatments for MRSA infections. These findings emphasize the importance of continuous surveillance of local MRSA resistance patterns to guide empirical treatment and improve clinical outcomes. Keywords: MRSA, Patients, pattern, SSTIs, Pathogen, Antibiotics